The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.2152/jmi.61.151
|View full text |Cite
|
Sign up to set email alerts
|

Indigo Carmine Dye-Assisted Lymphatic-Sparing Laparoscopic Palomo Varicocelectomy In Children

Abstract: : The ideal method for varicocelectomy in children remains controversial. We present our experience with dye-assisted lymphatic-sparing laparoscopic varicocelectomy (LSLV) in children, which overcomes the limitations of previously described techniques. Materials and methods : Five consecutive LSLVs were performed over a period of three years on children with a mean age of twelve years. The varicocele grade was three in one case and grade 2 in four cases, respectively. A left subdartos injection of 2 ml of Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The procedure is facilitated by the magnifying effect of the laparoscopic lens, which allows for excellent visualization of the structures of the vascular bundle. To achieve better visualization of the lymphatics, recent findings have shown that intra-dartos/intra-testicular injection of isosulfan blue is significantly better than the previously described intra-dartos injection, thereby allowing identification of lymphatic vessels in 100% of the cases in our series [43][44][45][46].…”
Section: Laparoscopymentioning
confidence: 71%
“…The procedure is facilitated by the magnifying effect of the laparoscopic lens, which allows for excellent visualization of the structures of the vascular bundle. To achieve better visualization of the lymphatics, recent findings have shown that intra-dartos/intra-testicular injection of isosulfan blue is significantly better than the previously described intra-dartos injection, thereby allowing identification of lymphatic vessels in 100% of the cases in our series [43][44][45][46].…”
Section: Laparoscopymentioning
confidence: 71%
“…Methylene blue was avoided because this dye may cause local tissue reactions. Ishibashi et al (23) used Indigo carmine because there has been extensive experience with this dye in cases of lymphatic mapping and sentinel node identification in cases of breast cancer. If 1-2 lymphatic channels were preserved during a varicocelectomy, there were no postoperative hydroceles.…”
Section: Resultsmentioning
confidence: 99%
“…Ishibashi et al . 82 used Indigo carmine because there has been extensive experience with this dye in cases of lymphatic mapping and sentinel node identification in cases of breast cancer. If 1–2 lymphatic channels were preserved during a varicocelectomy, there were no postoperative hydroceles.…”
Section: Refinementsmentioning
confidence: 99%